Socrates Digital for learning and problem solving - Salisbury, Mark (IGI Global, 2021)
"Readers of this book will learn how to build intelligent digital advisors that discern and provide the knowledge human users seek in fulfilling their responsibilities in the workplace through the aid of a new knowledge representation, called expert advice, that builds upon research in artificial intelligence, instructional design, cognitive psychology, and the learning sciences